Developing a Diabetes Knowledge Scale for Adults and its Psychometric Properties - EROL, SAİME (My University, 2022)
Objective: This study was conducted to develop and test the psychometric properties of a \"Diabetes Knowledge Scale for Adults.\"Methods: The sample for this research of methodological design consisted of 500 individuals, ages 18-90, who had presented at a state hospital in Istanbul during the period October 2018-April 2019 with or without a diagnosis of diabetes. Data for the study were collected with a \"Sociodemographic Characteristics Descriptive Questionnaire\" and the \"Diabetes Knowledge Scale for Adults (DKSA).\" The validity of the scale was evaluated with the content validity index and construct validity testing (exploratory, confirmatory factor analyses). Its reliability was assessed with KR-20 internal consistency analysis, item-total correlation testing, the item discrimination, item difficulty indexes, and test-retest analysis.Results: The content validity index for the 28-item scale was found to be 0.92. The exploratory factor analysis revealed five subscales that explained 62.15% of scale variance. The results of the confirmatory factor analysis, GFI= 0.88 CFI= 0.93, AGFI= 0.86, SRMR= 0.01 and chi 2/ df = 2.43, confirmed a good and acceptable level of goodness of fit for the scale. The scale\"s KR-20 reliability coefficient was 0.94, item-total correlations were above .45 and the correlation between the test-retests administered two weeks apart was found to be r=0.99Conclusion: DKSA is a valid and reliable scale that can be used to determine the knowledge level of between the ages of 18-90 adults about diabetes.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Health Sciences; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Diabetes; knowledge; scale; adult; validity; reliability; VALIDATION; VALIDITY; Diabetes; knowledge; scale; adult; validity; reliability